A decision analytic model to investigate the cost-effectiveness of poisoning prevention practices in households with young children - Achana, Felix; Sutton, Alex J.; Kendrick, Denise; Hayes, Mike; Jones, David R.; Hubbard, Stephanie J.; Cooper, Nicola J. (BioMed Central, 2016)
Background: Systematic reviews and a network meta-analysis show home safety education with or without the provision of safety equipment is effective in promoting poison prevention behaviours in households with children. This paper compares the cost-effectiveness of home safety interventions to promote poison prevention practices.